Ascertaining Curriculum Relevance through Web-based Tracer Study - Wilyanti, Liza Septa; Putra, Yoga Mestika; Wulandari, Sovia; Bansa, Yorina An'guna; Megawaty, Merti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2023)
This article aims to describe the relevance of alumni's field of work with the curriculum of the Indonesian Literature Study Program, Faculty of Teacher Training and Education (FKIP), Universitas Jambi. The research object was Indonesian Literature alumni who responded with a total of 86 respondents. The data collection technique was carried out by sharing the questionnaire link via the study program website https://sastraindonesia.unja.ac.id/ to 86 Alumni. The data in this research were analyzed using a descriptive approach. The findings show that graduates have worked with a high level of job suitability (41.9%). It indicates that the relevance of the curriculum to world needs is quite appropriate. The findings also show that most of the respondents worked as private employees. It can be concluded that the Indonesian Literature Study Program needs to equip graduates with recognition of competencies in certain fields for students. A certificate or competency certificate will be an added value for graduates to compete in the workplace.